The My Jump Lab application is a valid and reliable low-cost alternative to test curved sprint performance - Fílter, A.; Olivares-Jabalera, J.; Beltrán-Garrido, J. V.; Santalla, A.; Balsalobre-Fernández, C.; Gálvez, J.; De-la-Cruz-Torres, B. (Sports Biomechanics, 2025)
Curved sprinting has been proposed as a relevant and specific skill for soccer players` physical performance. However, professional timing systems are not always readily available in less resource-constrained environments. To address this issue, the development of a low-cost and user-friendly smartphone application could have practical applications for team sports staffs. In this context, the objective of this study was to evaluate the validity and reliability of the My Jump Lab application for the measurement of the curved sprint performance test. Correlational, comparative, and Bland-Altman analyses were conducted to assess the validity and reliability of the application in comparison with the gold-standard device. The results demonstrated excellent concurrent validity (r = 0.97-0.99, p < 0.001), and acceptable reliability (coefficient of variation < 3%, intraclass correlation coefficient = 0.88-0.96). Bland-Altman plots revealed small biases (-0.015 s and -0.010 s for the 17-m and 8.5 m curved sprints, respectively) and narrow 95% limits of agreement (-0.04 to 0.01 s and -0.03 to 0.01 s), indicating string agreement and no heteroskedasticity. Although small but significant differences were observed between test and retest sessions (p < 0.05), the overall findings support that My Jump Lab is a valid and reliable tool for assessing completion time during the curved sprint test in the specified arc, offering a cost-effective alternative for applied sport settings.